A Literature Review of Mobile Payments in Sub-Saharan Africa - Boateng, R. (International Working Conference on Transfer and Diffusion of IT, 2019)
The influx of mobile technologies during 1990’s saw to the purchase of mobile phones and subsequently mobile terminals in the form of tablets, PDAs among others. The trend in adoption has seen increasing hikes and drastic impact on business transactions also recorded. Mobile payments have emerged as one of the electronic payment platforms that are creating convenience for many consumers. In order to strengthen the field and to examine the knowledge gap over a decade (2007–2017), a review of literature was opportune. Hence 37 studies conducted in Sub-Saharan Africa were retrieved, classified based on TOE framework and Porter’s five competitive forces. The thematic areas identified based on the framework were reviewed. In addition, geographical cover, methodological issues, conceptual frameworks and gaps identified for further studies were also studied. The analysis showed that, similar to earlier findings; Changes in technology, merchant adoption and consumer adoption have been well researched into with grey areas like traditional payment systems, socio-cultural factors that affect implementation of mobile payment system. The research gaps and direction of future research were discussed.
Research Article
Keywords: Mobile phone; Sub-Saharan Africa; Mobile payment services market; M-commerce; Mobile money; Ghana